Exploring specific features of Transport Interchange Hubs (TIH) design, taking into account the climatic conditions of the Russian Arctic - Dunichkin, Ilya V.; Bleil de Souza, Clarice; Bogachev, Konstantin; Pezzica, Camilla (Springer, 2019)
This paper provides a more detailed analysis of the context of designing Transport Interchange Hubs (TIHs) in the Arctic Zone of the Russian Federation (AZRF). It uses a design framework proposed by another paper also presented in this conference by the same authors [1] to discuss how green spaces can be inte-grated to TIHs in extreme climates to enhance the qualities of different types of spaces inside terminals considering implications of these in the overall assess-ment of building performance. It also discusses, the way pedestrian flow and movement is modelled and simulated in Russia in relation to the different simula-tion techniques used in other countries (mainly the West) and what are the ad-vantages these different models offer in the assessment of design decisions for TIHs in the AZRF considering how these could potentially be integrated with parametric design tools, finishing by highlighting complexities involved in de-signing compact buildings, a necessary requirement to reduce heat losses and the impact of building footprint on the permafrost. As the AZRF is now experiencing unprecedented economic development and completely lacks transport integrated facilities (TIHs) this paper attempts to review and discuss specific features of these buildings so new developments currently planned for the Russian Arctic can be better designed and assessed mainly in relation to pedestrian flow and their integration with opportunity spaces to improve the quality of passengers’ waiting time.